Polskie Tłumaczenia Filmowe (Translating films in Polish) - Garcarz, Michał (The Journal of Specialised Translation, 2006)
The main objective of this paper is to demonstrate the general characteristics of three translation methods which are applied for the purpose of film translation in the TV corporations in Poland. This highly theoretical paper is addressed both to translation theoreticians, as well as to audiovisual translators-practitioners whose professional interests concentrate on the central European TV translation market in particular.